INTEGRATING LOCAL CULTURE IN ENGLISH LEARNING: DEVELOPING ESP MATERIALS FOR ARTS EDUCATION STUDENTS - Amalia, Novika; Nugraha, Richard Ferry; Fikri, Muhammad Subhan; Farid, Rezqan Noor (Journal of English Educational Study (JEES), 2025)
This study aims to design a culturally-based English textbook for Performing Arts Education students. The research applies Culturally Relevant Pedagogy (CRP) and Content and Language Integrated Learning (CLIL) to the ADDIE framework to improve English competence and local culture appreciation. A needs analysis of 36 students found that 82.35% have basic English skills and low speaking confidence. Multimedia elements, culturally relevant themes, and practical ways integrating English learning to artistic surroundings were popular with students. Experts validated content relevancy and linguistic accuracy but suggested simplifying idioms and adding cultural examples for accessibility. Two chapters' initial trials were moderately effective, scoring 3.39 for relevance and 3.89 for clarity. Changes improved cultural integration and interactivity. Two trials with six amended chapters showed considerable gains in clarity and relevance, scoring 4.53 and 4.17, respectively. Contextual vocabulary, realistic grammar exercises, and local-global cultural balance impressed students. The study found that CRP and CLIL in ESP materials improve English and cultural awareness. Long-term effects and digital tools for accessibility and interaction should be further explored.